ANALISIS ALOKASI ANGGARAN PENDIDIKAN DALAM ANGGARAN PENDAPATAN DAN BELANJA DAERAH KOTA SAMARINDA PERIODE 2017-2021 - Putri Tartilla , Rindiriani Tirana; Rachim , Abdul; Rahayu, Vitria Puri (Faculty of Teacher Training and Education, Mulawarman University, 2023)
The research entitled Analysis of Education Budget Allocations in the Samarinda City Regional Revenue and Expenditure Budget for the 2017-2021 Period was carried out under the guidance of Mr. Prof. Dr. Abd. Rachim AF, S.E., M.Sc. as Supervisor I and Mrs. Vitria Puri Rahayu, S.Pd., M.Pd. as Supervisor II. The aim of this research is to find out the education budget in the Samarinda City APBD for 2017-2021, analyze and describe the proportion of the education budget in the Samarinda City APBD for 2017-2021. This research uses descriptive research with a quantitative approach. This research uses the entire population as a sample, namely time series data on the Samarinda City education budget for 2017-2021. The type of data in this research uses secondary data obtained from BPKAD Samarinda City. The data analysis technique used in this research uses the education budget proportion formula. The research results show that the education budget allocation for 2017-2021 has reached 20% except in 2020. The education budget in the research year was mostly used for indirect spending.